Product Market Regulation and Labor Market Outcomes: How can Deregulation Create Jobs? - Michael Burda (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper reports on ongoing research on the interactions between product regulation and labor market outcomes. In particular, I summarize work on the employment effects of shop-closing regulation in the retail and other related sectors. Evidence on employment in the retail sector from Germany, the Netherlands and the United States suggests that the regulatory regime might play an important role; I argue that a nonnegligible comp o nent of the recent Dutch employment miracle could be attributed to product market deregulation, in particular liberalization of shop-closing laws effected in the mid-1990s. I sketch a model, based on Burda and Weil (1999), which can rationalize potential public interest aspects of such regulations as well as identify their employment and output costs.
Keywords: 330; Product market regulation; retail trade; employment